Substantially impervious lithium super ion conducting membranes - NIMON YEVGENIY S; DE JONGHE LUTGARD C; VISCO STEVEN J (2014)
A composite solid electrolyte includes a monolithic solid electrolyte base component that is a continuous matrix of an inorganic active metal ion conductor and a filler component used to eliminate through porosity in the solid electrolyte. In this way a solid electrolyte produced by any process that yields residual through porosity can be modified by the incorporation of a filler to form a substantially impervious composite solid electrolyte and eliminate through porosity in the base component. Methods of making the composites are also disclosed. The composites are generally useful in electrochemical cell structures such as battery cells and in particular protected active metal anodes, particularly lithium anodes, that are protected with a protective membrane architecture incorporating the composite solid electrolyte. The protective architecture prevents the active metal of the anode from deleterious reaction with the environment on the other (cathode) side of the architecture, which may include aqueous, air and organic liquid electrolytes and/or electrochemically active materials.